The THE INFLUENCE OF CHLORPROMAZINE HYDROCHLORIDE ON THE SIZE OF SMALL UNILAMELLAR DIMYROSTYLPHOSPHATIDYLCHOLINE LIPOSOMES AS REVEALED BY LIGHT SCATTERING PHOTOMETRY - FARAH, FARAH HAMAD (International Journal of Applied Pharmaceutics, 2019)
Objectives: This study aims to investigate the possible influence of the model, cationic, surface-active solute chlorpromazine hydrochloride (CPZ-HCl) on the size of small unilamellar dimyristoyl phosphatidylcholine (DMPC) liposomes as a function of temperature and CPZ-HCl concentration, below and above the critical micelle concentration (CMC). Methods: Small unilamellar DMPC liposomes were prepared by dissolving DMPC in chloroform and the solvent was rota-evaporated in a water bath adjusted at 40 °C. The lipid film was then dispersed in 0.1 M KCl solution adjusted at pH 6.2 to form large multilamellar liposomes which are then sonicated and fractionated via Sepharose 2B-Cl gel. The elution profile was followed spectrophotometrically at λ 260 nm. Combined fractions from the trailing edge of the included peak which is due to small unilamellar liposomes, were used as a source throughout this study. The SOFICA light scattering photometer (Model 42000) was used to determine the weight average liposomes weight (Lw) of small unilamellar DMPC liposomes. The Lw was determined in the absence and presence of CPZ-HCl both above and below the CMC over the temperature range of 25 °C to 40 °C. Results: The Lw was observed to increase linearly in the absence and presence of CPZ-HCl. The Lw was observed to increase linearly in the absence of CPZ-HCl, from 1.88×106+0.02 g/mol at 25 °C to 3.25×106+0.03 g/mol at 40 °C. Similarly, the Lw was observed to increase linearly in the present of CPZ-HCl, for example at 18 mmol drug concentration, the Lw increases from 11×106+0.04 g/mol at 25 °C to 13.75×106+0.03 g/mol at 40 °C. When the data are presented as a function of CPZ-HCl concentration, a gradual increase in Lw was observed below the CMC. Little increase in Lw however, was observed at post-micellar concentrations of 14 mmol and 18 mmol.